Phenomenon - Turteltaub, Jon.; Brent, Spiner; Forest Whitaker; Jeffrey DeMunn; Kyra Sedgwick; Richard Kiley; Robert Duvall; John Travolta (USA Touchstone Pictures, 1996)
The main character (John Travolta) observes a strange light on his birthday at a bar. The following days he becomes very intell-i-gent and puts the intell-i-gence to good use in his community. When word gets around he becomes known as a freak and everyone wants to figure out why this happened to a car mechanic. The government also wants to get their hands on it to put it to other uses.
An ordinary man sees a bright light descend from the sky, and discovers he now has super-intelligence and telekinesis.
Gerald Di Pego
Languages : English, Portuguese
Subtitles : English, Turkish, Russian, Estonian
Keywords: Fantasy; Romance; Drama